Faktor-faktor yang Memengaruhi Perencanaan Anggaran Pendapatan Asli Daerah: Komitmen Organisasi, Produk Domestik Regional Bruto, dan Jumlah Penduduk - Cris Kuntadi; Frenadi Irianto; Herty Safitry Yunintasari (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article aims to review the factors that influence regional own-source revenue (PAD) budget planning, namely organizational commitment, gross regional domestic product (GDP) and population, a literature study on State Financial Management. This article is a literature review intended to build hypotheses about the influence of variables for use in further research. The results of this literature review article are organizational commitment, GRDP and population that influence PAD budget planning.